RNA interference to enhance radiation therapy: Targeting the DNA damage response. (28th December 2018) - Ratnayake, G.; Bain, A.L.; Fletcher, N.; Howard, C.B.; Khanna, K.K.; Thurecht, K.J.
Abstract: RNA interference (RNAi) therapy is an emerging class of biopharmaceutical that has immense potential in cancer medicine. RNAi medicines are based on synthetic oligonucleotides that can suppress a target protein in tumour cells with high specificity. This review explores the attractive prospect of using RNAi as a radiosensitiser by targeting the DNA damage response. There are a multitude of molecular targets involved in the detection and repair of DNA damage that are suitable for this purpose. Recent developments in delivery technologies such nanoparticle carriers and conjugation strategies have allowed RNAi therapeutics to enter clinical trials in the treatment of cancer. With further progress, RNAi targeting of the DNA damage response may hold great promise in guiding radiation oncology into the era of precision medicine. Highlights: RNA interference (RNAi) is an emerging therapy that can precisely suppress proteins in a tumour cell. Proteins involved in the detection and repair of DNA damage can be targeted by RNAi to sensitize cancers to radiotherapy. Newly developed delivery platforms are surmounting the obstacles to the clinical translation of RNAi.